1987
DOI: 10.1002/ijc.2910400505
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer among Chinese women

Abstract: A case-control study involving interviews with 672 female lung cancer patients and 735 population-based controls was conducted to investigate the high rates of lung cancer, notably adenocarcinoma, among women in Shanghai. Cigarette smoking was a strong risk factor, but accounted for only about one-fourth of all newly diagnosed cases of lung cancer. Most patients, particularly with adenocarcinoma, were life-long non-smokers. The risks of lung cancer were higher among women reporting tuberculosis and other pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
202
3
6

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(230 citation statements)
references
References 15 publications
19
202
3
6
Order By: Relevance
“…Regardless of the accuracy of the estimates, cooking in highly urbanized areas is a major source of acrolein in the atmosphere. Epidemiological findings indicate that emission of acrolein from wok cooking rather than tobacco smoking is linked to the high incidence of lung cancer in Chinese women [31]. A study conducted by Shields and co-workers [32] determined the acrolein emissions from wok cooking to be highest for unrefined Chinese rapeseed oil and lowest for peanut oil.…”
Section: Lipids As a Source Of Acroleinmentioning
confidence: 99%
“…Regardless of the accuracy of the estimates, cooking in highly urbanized areas is a major source of acrolein in the atmosphere. Epidemiological findings indicate that emission of acrolein from wok cooking rather than tobacco smoking is linked to the high incidence of lung cancer in Chinese women [31]. A study conducted by Shields and co-workers [32] determined the acrolein emissions from wok cooking to be highest for unrefined Chinese rapeseed oil and lowest for peanut oil.…”
Section: Lipids As a Source Of Acroleinmentioning
confidence: 99%
“…In all, 31 studies were identified that provided risks of lung cancer stratified by family history of the disease (Tokuhata and Lilienfeld, 1963a, b;Lynch et al, 1982;Ooi et al, 1986;Samet et al, 1986;Gao et al, 1987;Kramer et al, 1987;Sellers et al, 1987;Tsugane et al, 1987;Horwitz et al, 1988;Wu et al, 1988Wu et al, , 1996McDuffie et al, 1989;Wu-Williams et al, 1990;Liu et al, 1991;McDuffie, 1991;Osann, 1991;Shaw et al, 1991;Pavlakou et al, 1993;Schwartz et al, 1996Schwartz et al, , 1999Wang et al, 1996;Brownson et al, 1997;Kreuzer et al, 1998;Mayne et al, 1999;Bromen et al, 2000;Wunsch-Filho et al, 2002;Etzel et al, 2003;Wu et al, 2004;Jin et al, 2005;Matakidou et al, 2005). Three studies (Lynch et al, 1982;Sellers et al, 1987;Schwartz et al, 1999) were excluded from the review as the same data were duplicated in subsequent studies.…”
Section: Case -Control Studiesmentioning
confidence: 99%
“…[7][8][9] The protective effect of dietary fruit and vegetable in the development of lung cancer has been of considerable interest since it was first described in the 1970s. 10 Recent studies support an effect of total fruit and vegetable intake rather than of individual micronutrients, 11 with the evidence being most consistent for Brassica vegetables, which are rich in isothiocyanates, potent inhibitors of NNK carcinogenesis.…”
mentioning
confidence: 99%